Using the principles of 'same day emergency care' in our new acute medical unit. (2020) - Visanji, Shaznin; Lyne, Holly; Phillips, Alexandra; Gilbert, Hazel; Ferguson, Zachary; Hawksley, Amber; Barker, Robert
No abstract available